2012
DOI: 10.1248/cpb.60.499
|View full text |Cite
|
Sign up to set email alerts
|

Caffeic Acid Oligomers with Hyaluronidase Inhibitory Activity from <i>Clinopodium gracile</i>

Abstract: Eight new caffeic acid oligomers, clinopodic acids J-Q (1-8), were isolated from whole plants of Clinopodium gracile, together with nine known caffeic acid oligomers. The caffeic acid oligomers with two to four dihydrobenzofuran rings were isolated as natural products for the first time. Clinopodic acid M (4) showed the strongest hyaluronidase inhibitory activity, IC 50 (19 µM) among the 22 compounds isolated from this plant.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 25 publications
1
15
0
Order By: Relevance
“…Rosmarinic acid had anti-hyaluronidase activity with IC 50 of 309 µM, while its dimers, identified as rashomonic acid C, rashomonic acid D, meehanioside A, meehanioside B, meehanioside C and meehanioside D, also showed considerable anti-hyaluronidase activity with IC 50 of 275, 183, 1049, 873, 924 and 781 µM, respectively. Aoshima et al [ 44 ] evaluated the anti-hyaluronidase activity of caffeic acid oligomers isolated from Clinopodium gracile , and among the isolated compounds, clinopodic acid M revealed the strongest activity with an IC 50 of 19 µM.…”
Section: Hydroxycinnamic Acidsmentioning
confidence: 99%
“…Rosmarinic acid had anti-hyaluronidase activity with IC 50 of 309 µM, while its dimers, identified as rashomonic acid C, rashomonic acid D, meehanioside A, meehanioside B, meehanioside C and meehanioside D, also showed considerable anti-hyaluronidase activity with IC 50 of 275, 183, 1049, 873, 924 and 781 µM, respectively. Aoshima et al [ 44 ] evaluated the anti-hyaluronidase activity of caffeic acid oligomers isolated from Clinopodium gracile , and among the isolated compounds, clinopodic acid M revealed the strongest activity with an IC 50 of 19 µM.…”
Section: Hydroxycinnamic Acidsmentioning
confidence: 99%
“…Some cis-oriented LA analogues have been reported from natural sources, e.g., cis-lithospermic acid from S. yunnanensis C. H. Wright [23] and clinopodic acid N from Clinopodium gracile (Benth.) O. Kuntze [24]. However, there was insufficient discussion about the absolute configuration, and ECD data from these analogues in previous reports.…”
Section: Resultsmentioning
confidence: 97%
“…3). In many compounds with (S)-amide (10) (R)-amide (11 dihydrobenzofuran moieties, the configurations at C-7 were determined from the 220-240 nm region [24,25]. However, it has not been demonstrated whether this empirical rule is applicable to the C-7 configuration in the dihydrobenzofuran moieties of isolates (1-3 and 7).…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, evaluation of HAase inhibition could be valuable for identification of compounds with anti-inflammatory activity. Many studies have reported HAase inhibition activity as a measure of anti-inflammatory activity in compounds, including caffeic acid oligomers from Clinopodium gracile [3], phlorotannins of brown algae [19], pentacyclic triterpenoids from Prismatomeris tetrandra [24], flavonols in processed onion [10], naringenin [23], and in soybeans and sword beans fermented with Bacillus subtilis [13].…”
Section: Introductionmentioning
confidence: 99%